Long-term survival among OHCA patients who survive to 30 days: Does initial arrest rhythm remain a prognostic determinant? - Majewski, David; Ball, Stephen; Bailey, P.; Bray, Janet; Finn, Judith (ELSEVIER IRELAND LTD, 2021)
Objective: To determine whether initial cardiac arrest rhythm remains a prognostic determinant in longer term OHCA survival. Methods: The St John Western Australian OHCA database was used to identify adults who survived for at least 30 days after an OHCA of presumed medical aetiology, in the Perth metropolitan area between 1998 and 2017. Associations between 8-year OHCA survival and variables of interest were analysed using a Multi-Resolution Hazard (MRH) estimator model with 1-year intervals. Results: Of the 871 OHCA patients who survived 30 days, 718 (82%) presented with a shockable initial arrest rhythm and 153 (18%) presented with a non-shockable rhythm. Compared to patients with initial shockable arrests, patients with non-shockable arrests experienced increased mortality in the first (HR 3.33, 95% CI 2.12−5.32), second (HR 2.58, 95% CI 1.22−5.15), third (HR 2.21, 95% CI 1.02−4.42) and fourth (HR 2.21, 95% CI 1.02−4.42) year post arrest; however, in subsequent years the initial arrest rhythm ceased to be significantly associated with survival. The overall 8-year survival estimates after adjustment for peri-arrest factors (as potential confounders) were 87% (95% CI 77–93%) for shockable arrests and 73% (95% CI 55–86%) for non-shockable arrests. Conclusions: Patients with non-shockable (as opposed to shockable) initial arrest rhythms experienced higher mortality in the first 4-years following their OHCA; however, after four years the initial arrest rhythm ceased to be associated with survival.